La santé en ligne - Hélène Romeyer (Communication)
Based on the analysis of eight Internet sites in France, this article aims firstly to underline the extreme heterogeneity of the health information provided online. The author then examines the status of the information providers, the kinds of content, its quality and the role of these websites. The overall question is why, despite all the critics, more and more people seek information on these websites.